2012
DOI: 10.1007/s10661-011-2501-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Detection of bacterial endotoxin in drinking tap and bottled water in Kuwait

Abstract: This study was carried out to measure and compare the concentration of bacterial endotoxin in a variety of samples from drinking tap and bottled water available in Kuwait by using the Limulus Amoebocyte lysate test. A total of 29 samples were tested. Samples were collected from a variety of locations throughout the six governorates of Kuwait and 23 brands of local and imported bottled water samples were collected from the local market. The concentration of bacterial endotoxin was measured by using the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Failure to detect feacal/thermotolerant coliforms and a very low incidence of E. coli in imported bottled water samples tested may mean that the samples are free from feacal contamination and that the bottled water may be microbially safe for consumption by the public (Abdulraheem et al, 2012;Ahmad and Bajahlan, 2009;Al-Omran et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Failure to detect feacal/thermotolerant coliforms and a very low incidence of E. coli in imported bottled water samples tested may mean that the samples are free from feacal contamination and that the bottled water may be microbially safe for consumption by the public (Abdulraheem et al, 2012;Ahmad and Bajahlan, 2009;Al-Omran et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Semerjian (2011) investigated the levels of physicochemical of water then compared the results with Lebanese institution standards for bottled water. Abdulraheem, et al, (2012) measured and compared bacterial concentration of endotoxin in a variety of samples of tap and bottled water in Kuwait by using the Limulus Amoebocyte lysate test. They found that the drinking bottled water has less endotoxin compared to the tap water.…”
Section: Introductionmentioning
confidence: 99%